Optimization of Statin Production from Aspergillus tamarii - Anilkumar, Nidhiya Kizhakkootayil; Krishna, Arya Radhakrishnan; Chockalingam, Jayaprabha; Balakrishnan, Lavanya; Janarthanan, Navitha Thanu; Ramachandran, Praveen; Palanisami, Sharba Deepa; Dhanaraj, Sharmila Srimathi; Joseph, Sindhya; Jayalekshmi, Swathy Krishna; Antony, Trisha Mary Pandipilly; Ramasamy, Suganthi (Asian Journal of Biological and Life Sciences, 2020)
The present investigation was focused on screening of Lovastatin production using different agro-based wastes and augment the lovastatin production by isolating Aspergillus tamarii using response surface methodology (RSM) conducting statistical design such as Plackett - Burman design (PB) and Box - Behnken design (BB). Substrates such as rice husk, wheat bran, corn and sorghum bran were initially screened for evaluation of effective lovastatin production using Aspergillus tamarii under solid state fermentation (SSF). Among different substrates, wheat bran was the best substrate for lovastatin production proving highest yield of statin was 100 μg/ml. Further with submerged fermentation, the yield of statin was 96 μg/ml when glucose and lactose were used as a substrate. Thus, Aspergillus tamarii has the potential to be the source of statin production and can be used in different therapeutic applications.
Keywords: Aspergillus tamarii; Box- Behnken (BB); Optimization; Response surface methodology (RSM); Statin